Reduction of COD and color of acid and reactive dyestuff wastewater using ozone - Choi, JW; Song, HK; Lee, W; Koo, KK; Han, C; Na, BK (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2004)
Wastewaters obtained from bromamine acid dye and reactive dye manufacturing were treated by ozone bubbling in a cylindrical batch reactor for the purpose of reducing COD to below 150 mg/L, which is the environmental discharge standard of the Republic of Korea. Remarkable COD reduction and decolorization were observed at pH over 11. High inlet gas flowrate and high concentration of ozone gave better results. Little precipitation was observed under the conditions of remarkable COD reduction. At pH of 11, 15 LPM of inlet gas flowrate and 89.3 g/Nm(3) of ozone flowrate, the COD of bromamine acid dyestuff wastewater was reduced to 95 mg/L after 90 minutes, and the COD of reactive dyestuff wastewater was reduced to 120 mg/L after 120 minutes. Decolorization was completed after 30 minutes of reaction.
Keywords: HYDROGEN-PEROXIDE; FENTON OXIDATION; CONGO-RED; REMOVAL; KINETICS; ADSORPTION; DEGRADATION; MECHANISM